PRAGMATIC PRESUPPOSITION MAIN CHARACTERS IN THE ANIMATION MOVIE BIG HERO 6 - Damanik, Sintia; Sipayung, Kammer Tuahman; Sidabutar, Usman (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
A good and appropriate presumption can help find the right word variation before saying something in interaction and communication. Therefore, research on presuppositions in the formation of meaning in an interaction. By referring to Yule's theory (1996), this study aims to identify the types of pragmatic presuppositions found in the main characters in the animated film Big Hero 6. The data of this study were taken from the dialog of the main characters in the animated film Big Hero 6. In collecting the data, the researcher used the observation method. The findings of this study show that 27 data fulfill the six types of presupposition, namely existential presupposition (2), lexical presupposition (4), factual presupposition (2), structural presupposition (17), counterfactual presupposition (1), and non-factive presupposition (1).